THE QUR'ANIC PERSPECTIVE ON DISASTER SEMIOTICS - Mardan Mardan (Faculty of Adab and Humanities - Alauddin State Islamic University of Makassar, 2018)
This research entitled The Qur'anic Perspective on Disaster Semiotics. It uses interpretive approach with the method of tafsīr maudū'ī